How giving affects giving: a long-term analysis of donations. Issue 21 (3rd May 2018) - Habibpour, Mohammad M.; Peiffer, Mathieu; Pepermans, Roland; Jegers, Marc
ABSTRACT: Social preferences theories suggest that at least some people show altruistic behaviour. However, this philanthropic behaviour ranges from pure altruistic preferences to reluctant altruists. The fact that a subset of contributors has impure preferences raises questions regarding the stability of prosocial contributions. Assuming differences in other regarding preferences, we examine whether at an aggregated level monetary contributions are stable or fragile over time. We study the aggregated donations in the US from 1973 to 2013 using ARIMA and ARMAX models. The significant autoregressive and moving average coefficients in our estimations suggest that aggregated donations are highly autocorrelated. Our estimated impulse response functions indicate that aggregated donations converge to their historic mean quickly after an exogenous shock, which shows the stickiness of the inclination to donate.